2014
DOI: 10.1086/677541
|View full text |Cite
|
Sign up to set email alerts
|

How Important Are Hemoparasites to Migratory Songbirds? Evaluating Physiological Measures and Infection Status in Three Neotropical Migrants during Stopover

Abstract: Long-distance migrations are energetically expensive for many animals, including migratory songbirds. During these demanding journeys, birds likely face limitations in allocating resources to different physiological functions, including lipid reserves needed to fuel the migration and costly immune defense against pathogens. We sampled three species of long-distance migratory songbirds during their fall migration through coastal Georgia and quantified their body condition, subcutaneous fat reserves, and infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
1
21
1
Order By: Relevance
“…Interestingly, these results have varied. Some researchers have reported that parasites elevate H/L or N/L ratios (Fokidis, Greiner, & Deviche, ; Shutler & Marcogliese, ; Wojczulanis‐Jakubas et al., ), whereas others found no evidence of such (Cornelius et al., ; Granthon & Williams, ; Krams et al., ; Shutler, Lowe, & Robinson, ; Sperry et al., ). We note, however, that the interpretation of leucocyte profiles in the context of parasites can be subject to the same difficulties outlined above for coloration (see also Blaustein et al., ); in other words, high H/L ratios have been interpreted by some researchers as heightened ability to control and clear parasite infections, and by others as evidence of active infection.…”
Section: Use Of Leukocyte Profiles Over the Past Decadementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these results have varied. Some researchers have reported that parasites elevate H/L or N/L ratios (Fokidis, Greiner, & Deviche, ; Shutler & Marcogliese, ; Wojczulanis‐Jakubas et al., ), whereas others found no evidence of such (Cornelius et al., ; Granthon & Williams, ; Krams et al., ; Shutler, Lowe, & Robinson, ; Sperry et al., ). We note, however, that the interpretation of leucocyte profiles in the context of parasites can be subject to the same difficulties outlined above for coloration (see also Blaustein et al., ); in other words, high H/L ratios have been interpreted by some researchers as heightened ability to control and clear parasite infections, and by others as evidence of active infection.…”
Section: Use Of Leukocyte Profiles Over the Past Decadementioning
confidence: 99%
“…The hypothesis typically tested is that higher parasite loads are associated with higher H/L or N/L ratios (e.g. Cornelius, Davis, & Altizer, 2014;Wojczulanis-Jakubas, Jakubas, Czujkowska, Kulaszewicz, & Kruszewicz, 2012); some studies have incorporated additional variables such as moult (Pap et al, 2011), predation (Raffel, Hoverman, Halstead, Michel, & Rohr, 2010) or sex (Waterman, Macklin, & Enright, 2014) to investigate more complex relationships. Interestingly, these results have varied.…”
Section: Us E Of Leuko C Y Te Profile S Over the Pa S T Dec Adementioning
confidence: 99%
“…Results from other studies seeking links between these parameters and hemosporidian infections have also yielded inconsistent results. Some have documented positive correlations (e.g., in total WBC counts; Ots & Horak, 1998, lymphocytes;Ellis et al, 2014;Krams et al, 2013;Ots & Horak, 1998, and heterophils;Ellis et al, 2014;Krams et al, 2013), whereas others documented either no effect or a correlation in the opposite direction (e.g., in total WBC counts; Cornelius et al, 2014;Schoenle et al, 2017;Biard, Monceau, Motreuil, & Moreau, 2015, lymphocytes;Cornelius et al, 2014, heterophils, and H:L ratio;Cornelius et al, 2014;. Considered in concert, these inconsistencies indicate that links between hemosporidian infections and total WBC cell count, heterophils, and lymphocytes are context dependent and not generalizable across host-parasite systems.…”
Section: **mentioning
confidence: 99%
“…The host immune response is energetically costly, using resources that could have been allocated to other functions (Cornelius et al, 2014). An over-reactive immune response can itself damage the host (Sorci, 2013).…”
Section: **mentioning
confidence: 99%
See 1 more Smart Citation